THE EFFECT OF VOLLEYBALL UNDERWEAR PASSING TRAINING USING WALL MEDIA ON UNDERWEAR PASSING ABILITY IN CHILDREN AGED 10-12 YAERS - Wiga Erpianti; Agus Sulastio; Aref Vai (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to understand the effect of underhand passing training using a wall as a medium on underhand passing ability in children aged 10-12 years. This study is an experimental study using the One Groups Pretest-Posttest Design method. The sample in this study were 15 athletes of the Putri Angin Kuantan Singingi Club aged 10-12 years. The instrument in this study was a volleyball underhand passing skill test for ages 10-12 years. Data analysis and testing of research hypotheses using the t-test analysis technique (t-test) using the SPSS 23 program, namely by comparing the mean between the pretest and posttest with the hypothesis acceptance criteria if the t count value is greater than the t table with a significance of 5%. The results showed that: Underhand passing training using a wall as a medium on underhand passing ability in children aged 10-12 years at the Putri Angin Kuantan Singingi Club had a significant effect. These results were proven by data analysis using prerequisite tests and hypothesis testing. The results of the hypothesis testing obtained in the study were t count = 10.614> t table = 2.145 and a significance value of 0.000 <0.05. These results indicate that the t count value is greater than the t table. It can be concluded that there is an effect of underhand passing using wall media on underhand passing ability in children aged 10-12 years at the Putri Angin Kuantan Singingi Club.